2015
DOI: 10.1016/j.humpath.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic characteristics of the placental basal plate in in vitro fertilization pregnancies: a possible association with the amount of bleeding in delivery

Abstract: The aim of the present study was to investigate the relationship between assisted reproductive technology procedures, the morphology of the basal plate of placentas, and amount of bleeding in deliveries. Fifty-five whole placentas (fresh-embryo transfer in the in vitro fertilization cycle [n = 6], frozen-thawed embryo transfer in the natural cycle [n = 13] or in the hormonal cycle [n = 10], and age-matched spontaneously conceived pregnancies [n = 26]) were retrospectively enrolled and histologically analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
3
31
2
Order By: Relevance
“…In either circumstance, the decidua is underdeveloped in association with restricted fetal growth . One article indicated the association of the thinned decidual layer with pregnancies after a FET in HRT cycles . This seemed to stand in contrast to the current findings that the birthweight of the HRT group was higher relative to the ovulatory group.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…In either circumstance, the decidua is underdeveloped in association with restricted fetal growth . One article indicated the association of the thinned decidual layer with pregnancies after a FET in HRT cycles . This seemed to stand in contrast to the current findings that the birthweight of the HRT group was higher relative to the ovulatory group.…”
Section: Discussioncontrasting
confidence: 91%
“…In this regard, the findings from the laboratory of Hamamatsu University in Japan are noteworthy. They revealed that the morphology of the placental basal plate in pregnancies following a FET that was conducted in HRT cycles differs when compared with a FET that was conducted in ovulatory cycles . More precisely, compared with a FET in ovulatory cycles, the placenta that was obtained from a FET in HRT cycles exhibited the thickened Rohr fibrinoid layer that is located between the villous structure and the extravillous trophoblast layer, concomitant with thinning of the decidual layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences have included significantly larger placental weight and higher placental weight/birthweight ratio (51); increased thickness and a higher incidence of hematomas (52, 53), and altered gene expression (54, 55). Nakamura et al (53) reported that the thickness of the Rohr fibrinoid layer and percent loss of decidua were both significantly highest in the hormonal cycles using thawed embryos, with z-scores of both measures positively correlating with the amount of bleeding at delivery.…”
Section: Discussionmentioning
confidence: 99%